Ethical Principles in Digital Palliative Care for Children: The MyPal Project and Experiences Made in Designing a Trustworthy Approach - Garani-Papadatos, Tina; Natsiavas, Pantelis; Meyerheim, Marcel; Hoffmann, Stefan; Karamanidou, Christina; Payne, Sheila A. (Frontiers in Digital Health, 2022)
The opportunity to offer improved patient reported outcome (PRO) systems addressing personal needs of pediatric cancer patients, their parents and caregivers, has been an important technological advance of digital health, aiming to complement traditional methods of support in serious or terminal illness. This intersection of palliative care and technology may lead to significant improvements towards this direction and contribute to generation of valuable evidence, essential for the improvement of health care. This opportunity has been explored in the MyPal research project (https://mypal-project.eu/ funded by the European Commission), which aims to assess a patient-centered service for palliative care by improving electronic patient-reported outcome (ePRO) systems, relying on the adaptation and extension of digital health tools and concepts available from previous projects. The project is built around a study addressed to pediatric cancer patients and parents (MyPal4Kid) as well as a study addressed to adult patients (MyPal Adult) and health care professionals. Both development and implementation of e-PROs need to take place in a safe, secure and responsible manner, preventing any possible harm and safeguarding the integrity of humans. To that end, this paper aims to increase awareness of the ethical ramifications of new technologies and to address the ethical and normative challenges arising. The approach is constructed around the following principles: a) respect for the autonomy of participants, especially children, b) data protection and transparency, c) fairness and non-discrimination, d) individual wellbeing of participants in relation to their physical and psychological health status and e) accessibility and acceptability of digital health technologies for better engagement of users. These principles are adapted from the Ethics Guidelines for a trustworthy Artificial Intelligence (AI) which provide the framework for similar interventions to be lawful, complying with all applicable laws and regulations, ethical, ensuring compliance to ethical principles and values and robust, both from a technical and social perspective.